Compatibility of Jatropha Curcas in an Agroforestry System - Abugre, Simon (2015)
A Thesis submitted to the, Department of Agroforestry, Faculty of Renewable Natural Resources, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the degree of DOCTOR OF PHILOSOPHY IN AGROFORESTRY.